(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The freshwater Stinging catfish locally known as Shingi (Heteropneustes fossilis) is exposed to various concentrations of analytical grade FeSO4.7H2O. The LC50 values for Fe2+ were found to be 109, 68 and 45 mg/l at 24, 48 and 72 hrs, respectively indicating that the toxicity increased with time. Gills appear to be the first target organ for iron toxicity followed by the liver and muscle. Moisture contents in fish tissue increased due to release of the toxicant by biological way. Protein and lipid contents are decreased and ash content is increased with the increase of exposure time. In contrast, iron is relatively nontoxic to Shingi fish at low dose, but long time exposure has adverse effects in fish tissue. Thus, exposure to iron salt at toxic level resulted in accumulation of iron in fish tissue. Hence, the consumption of this type of contaminated fish might have detremental effect on human health. However, this needs extensive study to make any final conclusion. Bangladesh Pharmaceutical Journal 18(2): 179-182, 2015